Asian cultural values and help-seeking: a cross-sectional study on compulsive sexual behavior - Pham, Hoang-Long; Nguyen, Vu Hoang Anh; Le, Cong Minh; Truong-Thai, Thanh-Ha; Vu-Thi, Quynh-Anh; Phan, Xuan-Phat; Nguyen-Vo, Hoa-Nhu; Hua, Thuy Doan; Nguyen-Duong, Bao-Tran; Ho, Cyrus Su Hui; Tran-Chi, Vinh-Long (Frontiers in Psychiatry, 2025)
BackgroundSexuality is a complex construct influenced by various social and cultural factors, and while sexual behavior is generally considered adaptive for physical and mental well-being, it can become uncontrollable and harmful, leading to Compulsive Sexual Behavior (CSB). Limited research has explored how Asian cultural values may mediate the psychological consequences of CSB and influence attitudes toward seeking professional psychological help. This study examines the relationships among CSB, Asian cultural values, and attitudes toward seeking professional psychological help (ATSPPH) in a Vietnamese context.MethodsThree scales were employed to gather demographic variables and self-reported data, including the Asian Values Scale – Revised, the Individual-Based Compulsive Sexual Behavior Scale, and Attitudes Toward Seeking Professional Psychological Help. The present study was evaluated utilizing the partial least squares-structural equation modeling (PLS-SEM) methodology.ResultsThe findings confirm significant relationships, with a lack of control and negative affect in CSB being negatively associated with freedom and flexibility in Asian values. Conversely, the negative consequences of CSB showed a positive relationship with these values. Crucially, both traditional and freedom-flexibility values were found to negatively predict openness to seeking professional help. The study also revealed that Asian cultural values play a significant mediating role between CSB and ATSPPH. Furthermore, behavioral factors such as the frequency of pornography use, sexual frequency, and having a stable sexual partner moderated these relationships.DiscussionThese results highlight the complex interplay of cultural beliefs and individual behavior, underscoring the need for culturally sensitive interventions for those struggling with CSB in Asian culture.